1999
DOI: 10.2134/jeq1999.00472425002800010016x
|View full text |Cite
|
Sign up to set email alerts
|

Charge Properties and Nitrate Adsorption of Some Acid Southeastern Soils

Abstract: Numerous studies have been conducted examining nitrate (NO3) leaching losses from agricultural land. Simulation models have been developed that allow one to predict the potential of NO3 to leach to groundwater. However, many of these models treat NO3 as a conservative tracer and do not evaluate surface chemistry. This study evaluated the surface charge properties and NO3 adsorption capacity of four acid southeastern subsoils. Significant anion exchange capacity and NO3 retention was found for two of the soils.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 0 publications
1
13
1
1
Order By: Relevance
“…The recalculated nitrate adsorption maxima ranged from 0.4 to 7.0 cmol kg-I, and were higher in the lower horizons of HPA and LHA, which had developed under moderate to moderately dry soil-moisture conditions and showed a high allophane content but a low total carbon content. The nitrate adsorption of the Andisols observed in the present study was much higher than those reported in Ultisols and Oxisols, which are rich in iron oxides (Cahn et al 1992;Eick et al 1999), and comparable to that in the Andisols rich in amorphous aluminum (Kinjo and Pratt 1971). Although we still need to clarify the relationship between nitrate adsorption and the surface charge properties of the soils as well as the effects of the pH, the coexistence of sulfate and other anions, temperature, and the penetration rate of water on nitrate retention, the potential capacity of Andisols to adsorb nitrate and retard nitrate movement should be taken into account in predicting the fate of nitrate in soils and the consequent mitigation of groundwater contamination.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…The recalculated nitrate adsorption maxima ranged from 0.4 to 7.0 cmol kg-I, and were higher in the lower horizons of HPA and LHA, which had developed under moderate to moderately dry soil-moisture conditions and showed a high allophane content but a low total carbon content. The nitrate adsorption of the Andisols observed in the present study was much higher than those reported in Ultisols and Oxisols, which are rich in iron oxides (Cahn et al 1992;Eick et al 1999), and comparable to that in the Andisols rich in amorphous aluminum (Kinjo and Pratt 1971). Although we still need to clarify the relationship between nitrate adsorption and the surface charge properties of the soils as well as the effects of the pH, the coexistence of sulfate and other anions, temperature, and the penetration rate of water on nitrate retention, the potential capacity of Andisols to adsorb nitrate and retard nitrate movement should be taken into account in predicting the fate of nitrate in soils and the consequent mitigation of groundwater contamination.…”
Section: Resultscontrasting
confidence: 80%
“…Many studies have been conducted to evaluate the surface-charge properties and nitrate retention of soils in tropical and subtropical regions with a high degree of weathering and that are rich in iron oxides and kaolinite (Kinjo and Pratt 1971;Mekaru and Uehara 1972;Ng Kee Kwong and Deville 1984;Bellini et al 1996;Toner et al 1989;Cahn et al 1992;Eick et al 1999;Warren and Kihanda 2001;Duwig et al 2003). Allophanic Andisols, which are derived from volcanic ash and developed under humid and temperate conditions, have both positive and negative variable charges that depend on solution pH and ionic strength (Wada 1989).…”
mentioning
confidence: 99%
“…The Langmuir adsorption isotherm was utilized in the two works, whereas nitrate adsorption capacities were determined between 0.4 and 7.0 mmol g -1 for Andisols and 1-5.4 9 10 -4 mmol g -1 for Oxisols. The nitrate adsorption of the Andisols is much higher than those reported in other works (Cahn et al 1992;Eick et al 1999), where adsorption capacities were comparable with Velloso (1975). Picollo et al (1991) studied nitrate uptake and growth regulation in plant systems.…”
Section: Introductionsupporting
confidence: 69%
“…However, nitrate retention has been reported to occur in variable charge subsoils (Kinjo et Pratt, 1971;Black and Waring, 1979;Wong et al, 1990;Cahn et al, 1992;Reynolds-Vargas et al, 1994;Hartemink et al, 1996;Eick et al, 1999;Qafoku et al, 2000;Qafoku and Sumner, 2002;Warren and Kihanda, 2001;Ryan et al, 2001;Lehmann et al, 2004;Rasiah et al, 2003;Donn and Menzies, 2005a;Feder and Findeling, 2007;Sansoulet et al, 2007;Wong and Wittwer, 2009). Among tropical soils, highly weathered Acrisols (Ultisols) contain large amounts of kaolinite and oxi-hydroxides, leading to exchange surfaces that may be either negatively or positively charged (Cochrane and Souza, 1985).…”
Section: Introductionmentioning
confidence: 99%